Study on the mechanical properties of GGBS-based geopolymer concrete with steel fiber by cluster and regression analysis - Parashar, Arun Kumar; Kumar, Ajay; Singh, Prakash; Gupta, Nakul (Asian journal of civil engineering. Building and housing, 2024)
The utilization of steel fiber in geopolymer concrete has emerged as a subject of recent investigation, encompassing wide-ranging impacts. The engineering parameters of geopolymer concrete and steel fiber-reinforced geopolymer concrete (SFRGPC) have been evaluated and compared through the utilization of industry-standard tests, including measurements of compressive strength, flexural strength, and tensile strength. The steel fiber percentages considered in this study vary from 0.25 to 1.25%, with an interval of 0.25%. The inclusion of fibers in GGBS-based geopolymer concrete resulted in improved strength characteristics. The addition of a 1% volume percentage of fibers resulted in an 8.51% increase in compressive strength, a 61.63% increase in splitting tensile strength, and an 11.07% increase in flexural strength. A strong positive association was observed between compressive strength and both split tensile strength and flexural strength. The correlation coefficients ( R 2 ) for the relationship between compressive strength and split tensile strength, as well as flexural strength, were determined to be 0.8012 and 0.8431, respectively. In this study, an investigation was conducted on the clustering of compressive strength and split tensile strength.